Vibration analysis of the rotating multilayer piezoelectric Timoshenko nanobeam. (December 2022) - Mohammadi, M.; Farajpour, A.; Moradi, A.; Hosseini, M.
Abstract: The vibration behavior of multilayers piezoelectric nanobeam is investigated in this study. The governing equations of rotating piezoelectric beams are obtained by utilizing the Timoshenko beam theory. The nonlocal continuum theory along with surface elasticity theory are handled to derive the differential governing equation of motion. The differential governing equation of motions is solved by employing the DQM. The results show a great correlation between the numerical results and the presented results in the literature. The results are obtained for four different boundary conditions such as cantilever nanobeam (clamped-free or CF), simply-simply (SS), clamped-simply (CS), and clamped-clamped (CC). The reaction of vibration frequencies to the change of different parameters such as the external voltage, the thermal stress, the angular velocity, etc. is investigated. The results show that the boundary condition type, thermal stress, and external voltage have a vital consequence on the vibration frequency. The results of this study can be appropriated to design and fabricated the nanodevices such as nanomotors, nano turbines, biosensors, nano-electromechanical systems, and micro-electromechanical systems (NEMS/MEMS) devices.